2016
DOI: 10.1002/jat.3309
|View full text |Cite
|
Sign up to set email alerts
|

Let‐7a modulates particulate matter (≤ 2.5 μm)‐induced oxidative stress and injury in human airway epithelial cells by targeting arginase 2

Abstract: Epidemiological studies show that particulate matter (PM) with an aerodynamic diameter ≤ 2.5 μm (PM2.5) is associated with cardiorespiratory diseases via the induction of excessive oxidative stress. However, the precise mechanism underlying PM2.5-mediated oxidative stress injury has not been fully elucidated. Accumulating evidence has indicated the microRNA let-7 family might play a role in PM-mediated pathological processes. In this study, we investigated the role of let-7a in oxidative stress and cell injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…In hippocampal HT-22 cells subjected to a cycle of hypoxia/reoxygenation, an increase in ROS production occurs that could be mediated by an increase in miR-200a-3p and miR-200b-3p expression, although the mechanism by which miR-200 miRNAs affect ROS production in neuronal cells is still unclear (205). In B2B human bronchial epithelial cells, it has been shown that members of the let-7 family are downregulated by oxidative stress and, in turn, let-7a overexpression protects cells from the oxidative damage-mediated death by reducing oxidative stress through the direct inhibition of arginase 2 (177). In human Huh-7 hepatocytes, let-7 miRNAs also protect cells from oxidative injury through the direct inhibition of BACH1, a key repressor of the cytoprotective enzyme heme oxygenase 1 (74).…”
Section: The Role Of Mirnas In Mental Stress and Neuropsychiatric Dismentioning
confidence: 99%
“…In hippocampal HT-22 cells subjected to a cycle of hypoxia/reoxygenation, an increase in ROS production occurs that could be mediated by an increase in miR-200a-3p and miR-200b-3p expression, although the mechanism by which miR-200 miRNAs affect ROS production in neuronal cells is still unclear (205). In B2B human bronchial epithelial cells, it has been shown that members of the let-7 family are downregulated by oxidative stress and, in turn, let-7a overexpression protects cells from the oxidative damage-mediated death by reducing oxidative stress through the direct inhibition of arginase 2 (177). In human Huh-7 hepatocytes, let-7 miRNAs also protect cells from oxidative injury through the direct inhibition of BACH1, a key repressor of the cytoprotective enzyme heme oxygenase 1 (74).…”
Section: The Role Of Mirnas In Mental Stress and Neuropsychiatric Dismentioning
confidence: 99%
“…China, during the winter of 2017, the concentration of PM2.5 was 60-90 µg/m 3 in Changchun, which reached 2-3 times that of other seasons in the same area (21), he concentration, composition and properties of the particles vary with the region and season. Our previous study found that PM2.5 contained numerous chemical components, including Al, Ca, Fe, K, Zn, Mg, polycyclic aromatic hydrocarbons, organic carbon and elemental carbon, of which Al and organic carbon were the most abundant in the PM2.5 samples in Changchun, China, during the winter (22). In the present study, the samples of PM2.5 were collected over five months in winter.…”
Section: Discussionmentioning
confidence: 64%
“…Because the expression levels of let‐7a are relatively higher in some normal cells than the expression levels in some cancer cells. [16c,17] These results indicated that the relative expression levels of cancer‐related miRNAs are different in cancer cells and normal cells. Thus, this novel method was viable to monitor changes in miRNAs expression levels in single cancer cells.…”
Section: Resultsmentioning
confidence: 99%